PROFIL M. tuberculosis PASIEN TB SENSITIF RIFAMPISIN TERHADAP LAMA WAKTU PENUNDAAN PEMERIKSAAN SPUTUM - Sulistiyawati, Indah; Fatimah, Siti; Rahayu, Nur Laila (Universitas Lambung Mangkurat, 2025)
Tuberculosis (TB) is an infectious disease that is currently still a serious health problem in society, both in terms of mortality rates, morbidity rates, diagnosis and its therapy rates. Sputum quality is an important component in laboratory examinations. The quality of sputum samples can affect the number of M. tuberculosis bacteria. This study aims to determine the differences in the morphological characteristics of M. tuberculosis bacteria with the length of time of delay in sputum sample examination. The study was conducted at the Klinik Utama Kesehatan Paru Masyarakat Purwokerto. The study used a descriptive method with a cross-sectional design. The sample population of this study were all suspected TB patients who underwent Molecular Rapid Technique (MRT) examinations at the Klinik Utama Kesehatan Paru Masyarakat Purwokerto (KKPM) in the January-June 2024. The research sampling technique was purposive sampling that met the inclusion criteria. The results of the study showed that the morphological characteristics of the M. tuberculosis bacteria vary in each sputum sample, based on differences in the quality of the sputum examined with a general description of the morphological characteristics of the bacteria, which have the form of monobacillus, diplobacillus and bacillus, solitary and in colonies, and are a type of Gram-positive bacteria. Keywords: Mycobacterium tuberculosis, MDR-TB. TCM test, GeneXpert